Composition of the Communist Party of Lithuania between October 1940 and June 1941 - Maslauskienė, Nijolė (Genocidas ir rezistencija, 1999)
After the Soviets occupied Lithuania the Communist Party of Lithuania (CPL) became the major power serving the interests of a new regime. Since October 1940, after the CPL had merged with the VKP(b), the CPL became the centre representing the USSR’s political interests in Lithuania. During the total purge of the CPL(b) the Party eliminated from its ranks the members who, according to the Soviets, were socially, politically or ideologically hostile to the regime or, simply, unreliable. Thus the invaders formed a typical Stalinist organisation – socially and ideologically united, strictly centralised and disciplined, time-serving and obedient. After the purge the organisation was incorporated into the USSR’s political system and served as an assiduous instrument implementing the policy of the regime in Lithuania. Soon a great number of communists from Russia followed the Red Army. Many of them were employed at the LSSR’s authorities, and during 1941, the CPL(b) gradually became an organisation of foreign communists and soviet functionaries.